The Concept Nuestra América [Our America] in José Martí - López-Civeira, Francisca (2019)
The article analyzes the process of construction of the concept “Nuestra América” [Our America] by José Martí, as well as its importance as a fundamental milestone in Marti’s continental strategy. The analysis of the reality and the problems of the independent Latin America seen in Mexico, Guatemala and Venezuela, as well as the examination of the North American (USA) society opened the possibilities for the elaboration of this concept, which conveyed a continental strategy for the overcoming of the internal problems and the external dangers